Urban Planning and Design Approaches for Redevelopment: Case of Indian Railway Stations Redevelopment - Abha Sharma; Meenakshi Dhote (International Journal of Urban Design and Development, 2026)
Urban society’s spatial and functional needs are reflected in the theories that revolve around planning and design. These theories evolve and shape urban policies that are the frameworks for the future. The practice of these theories differs across the world because of the unique history and geography of urban areas. However, theories encompass a wide range of subjects that occur repeatedly. It is important to understand and contextualise the theoretical discourse and to be pragmatic in it. Indian cities are undergoing redevelopment at an unprecedented pace and mode. Many central and state institutions are capitalising on their land. Indian Railways has undertaken the redevelopment of its railway stations. For this, guidelines as manuals have been formed to address aspects considered crucial for the station environment. This has been a novel initiative by the Railways as policies and strategies on redevelopment are far and few. The policy makers of redevelopment consider certain aspects crucial to address, and certain others are sidelined. What could be the reason for this? There are underrepresented sectors that fail to get into the mainstream policies on redevelopment. To understand this discrimination, a list of urban concerns was prepared through the discourse on urban issues in research Papers. The list was expanded by including concerns highlighted by theories on urban planning and urban design. This was considered as a list of factors with which Case studies of redeveloped Railway Stations were examined. It was concluded that some factors are not included in the policies or in the framework of guidelines. The reason could be difficulty in the proper understanding and articulation of these urban issues.
Keywords: Cities; Railway Land Development Authority; planning and design; redevelopment; urban planning